Self Care Management Activities to Improve Psychological Serenity of Cancer Patients - Anastasia Diah Larasati; Aditya Firman Nugroho; Maria Marlina Tei (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Cancer patients need intensive psychological assistance when undergoing the process of cancer treatment. Nurses have a duty to provide holistic nursing care, namely by handling psychological serenity in cancer patients. The purpose of making this study is to provide scientific information to nurses related to self care management activities that can be educated to patients in order to provide psychological calm while undergoing treatment independently. The design used was a literature review study, using various databased CINAHL, PubMed, Science Direct, Google Schoolar, and Medline. Searching for articles was carried out by collecting themes about Self Care Management, Nursing Activities and Psychological Serenity of cancer patients. The criterion for inclusion in the search for literature sources is the year the article was published, starting from 2010 to 2020, in English, and full article. Search keywords are self care management, nursing activities, self activities, self care, psychological serenity, and psychological problems. A total of 25 articles were analyzed and produced 6 themes, including sports, self-management through spiritual activities, shared care with health practitioners or fellow cancer survivors, implementing positive self talk, listening to instrumental music therapy, and doing art making and art therapy. The application of appropriate innovation selfcare management to the psychological symptoms of cancer patients can also help improve the Quality of Life of cancer patients.